2014
DOI: 10.1136/archdischild-2013-304159
|View full text |Cite
|
Sign up to set email alerts
|

Cholestasis and meconium ileus in infants with cystic fibrosis and their clinical outcomes

Abstract: Cholestasis is an uncommon condition in CF affecting only 5.7% of the screened newborn CF population. The greatest risk factor for developing cholestasis is the presence of MI. However, the presence of MI appears not to be associated with the development of CFLD. An effect of neonatal cholestasis on the development of CFLD cannot be excluded by this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…However, a recent large, single-center analysis of 401 CF infants over a 25-year period and other studies have found no difference in the percentage of patients with meconium ileus who developed CFLD compared with those without liver disease 20-22 . Our results suggest that a history of meconium ileus increases risk for a homogeneous US pattern.…”
Section: Discussionmentioning
confidence: 91%
“…However, a recent large, single-center analysis of 401 CF infants over a 25-year period and other studies have found no difference in the percentage of patients with meconium ileus who developed CFLD compared with those without liver disease 20-22 . Our results suggest that a history of meconium ileus increases risk for a homogeneous US pattern.…”
Section: Discussionmentioning
confidence: 91%
“…53 In addition to short-term nutritional and surgical complications, neonatal cholestasis is common. 69 In the long term, CF patients with prior MI have not been shown to differ in pulmonary function, nutritional status, or survival; however, they have higher rates of DIOS in addition to possible postsurgical complications. [70][71][72] Distal Intestinal Obstruction Syndrome DIOS is a CF-specific obstructive process beginning in the ileocecum secondary to an adherent, viscid fecal mass associated with dehydrated intestinal contents and densely packed mucus.…”
Section: Ileocolonic Disease Meconium Ileusmentioning
confidence: 95%
“…Its incidence among infants diagnosed with CF within a statewide newborn screening program is considered low at 5.7%, but is approximately 140-fold greater than that in the general population of term infants. 69,153 MI and complicated MI are significant risk factors for the development of cholestasis, with incidence greater than 25% in infants with MI. 69 In addition to jaundice, other features of CF-associated neonatal cholestasis are often nonspecific.…”
Section: Neonatal Cholestasismentioning
confidence: 99%
“…About 25% of infants with CF-associated meconium ileus will develop neonatal cholestasis. 93 Cholestasis in CFRLD is likely due to the increased viscosity of bile from CFTR dysfunction. Cholestasis not only leads to liver parenchymal inflammation and fibrosis but also limits the amount of bile acids available for digestion by decreasing the total bile acid content and overall concentration of bile in the small intestines.…”
Section: Cf-related Liver Diseasementioning
confidence: 99%